The relationship between job satisfaction and absenteeism : a study of the shop floor workers in a motor manufacturing plant - Mashonganyika, Oswald (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
This research hypothesises a statistical positive significant correlation between job satisfaction and absenteeism among the shop floor workers of a motor manufacturing plant in the impoverished province of the Eastern Cape in South Africa. According to the literature review, two schools of thought exist that argue on the nature of the relationship. One believes that absence from work is in some way a natural consequence of job dissatisfaction, i.e. arguing for a job satisfaction-absenteeism relationship. The second one argues for a no relationship, arguing that absence is a result of habitual behaviour and or behaviours influenced by socioeconomic factors such as poverty that affect the employees' ability and pressure to attend work. A sample of 150 workers was randomly selected from the 2500 shop floor workers. The Job Descriptive Index (lDI) questionnaires were used to measure the satisfaction index of the workers. The absence statistics for the sample workers were gathered from the organisation's Human Resources department and statistical tests for correlation and regression were conducted on the two variables - lDI and absence data. Contrary to the expectations of the study, the results showed that overall job satisfaction and absenteeism were not correlated. It concluded that the job dissatisfaction theory of absenteeism is empirically unsupportable and alternative conceptualisations of absence contributors and potentially fruitful research strategies are discussed.
Keywords: Job satisfaction -- South Africa -- Eastern Cape; Absenteeism (Labor) -- South Africa -- Eastern Cape; Automobile industry and trade -- South Africa -- Eastern Cape -- Employees; Industrial relations -- South Africa -- Eastern Cape